Assembly, network stability, and dominant function of bacterial communities in different habitats of a large shallow lake: The role of habitat generalists - Tianxu Zhou; Shuren Wang; Qinglong L. Wu; Jin Zeng (Ecological Indicators, 2025)
Microbial communities are fundamental drivers of biogeochemical processes within various habitats of lake ecosystems. While differences in bacterial community composition among habitats have been well documented, our knowledge about the roles of different groups of microbes in maintaining the diversity patterns remains limited. In this study, we investigated the diversity patterns and functional roles of bacterial communities and sub-communities (habitat generalists and habitat specialists) across different habitats (water column, suspended particles, and sediments) of a large, shallow freshwater lake, Taihu. Our results revealed distinct patterns in alpha diversity and pairwise dissimilarity among habitats. The sediment bacterial community exhibited the highest alpha diversity, whereas the particle-attached bacterial community showed the greatest pairwise dissimilarity. Community assembly processes varied among the three habitats: deterministic processes dominated in the sediment bacterial community, while stochastic processes prevailed in the free-living community. The stability and complexity of habitat networks followed similar patterns, with the sediment bacterial network being the most complex and stable, while the particle-attached bacterial network was the simplest and most fragile. We identified sub-communities, including habitat generalists and specialists, and compared their network roles across habitats. A higher number of core network nodes and betweenness centrality of habitat generalists were observed across different networks in comparison with specialists, highlighting the crucial role of generalists in stabilizing the habitat microbial communities. The dominant function of the habitat generalists, chemoheterotrophy, was positively associated with the network cohesion of different habitats, supporting the roles of the generalists in maintaining the stability of the community. This study provides new insights into microbial community assembly in lake ecosystems and highlights the critical roles of habitat generalists in maintaining bacterial network stability.